2023
DOI: 10.3201/eid2906.221755
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Seroprevalence and Cross-Variant Antibody Neutralization in Cats, United Kingdom

Abstract: Anthropogenic transmission of SARS-CoV-2 to pet cats highlights the importance of monitoring felids for exposure to circulating variants. We tested cats in the United Kingdom for SARS-CoV-2 antibodies; seroprevalence peaked during September 2021–February 2022. The variant-specific response in cats trailed circulating variants in humans, indicating multiple human-to-cat transmissions over a prolonged period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 14 publications
(15 reference statements)
3
14
0
Order By: Relevance
“…Several studies have demonstrated that SARS-CoV-2 viruses detected in companion animals correspond to concurrent locally dominant lineages circulating in the human population ( 8 , 26 ). In this study, we found that the prevalence of antibodies in these cats and dogs was also in line with that found in the human population of Thailand, consistent with a previous report ( 28 ). Previous sero-epidemiological studies have yielded data indicating a low infection rate of SARS-CoV-2 in Thai people in various risk groups in Bangkok and Chiang Mai Province of Thailand during the first year of the COVID-19 pandemic, which spanned the first two waves and part of the third wave of the COVID-19 outbreaks in Thailand ( 40 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Several studies have demonstrated that SARS-CoV-2 viruses detected in companion animals correspond to concurrent locally dominant lineages circulating in the human population ( 8 , 26 ). In this study, we found that the prevalence of antibodies in these cats and dogs was also in line with that found in the human population of Thailand, consistent with a previous report ( 28 ). Previous sero-epidemiological studies have yielded data indicating a low infection rate of SARS-CoV-2 in Thai people in various risk groups in Bangkok and Chiang Mai Province of Thailand during the first year of the COVID-19 pandemic, which spanned the first two waves and part of the third wave of the COVID-19 outbreaks in Thailand ( 40 ).…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies showed that the SARS-CoV-2 virus detected in companion animals corresponds to concurrent locally dominant lineages circulating in the human population ( 8 , 26 ). The antibody response to the SARS-CoV-2 virus in cats in the United Kingdom followed circulating SARS-CoV-2 variants in humans ( 28 ). It indicated that long-term multiple contact between humans and companion animals could cause pathogen spillover.…”
Section: Introductionmentioning
confidence: 99%
“…As with all studies of SARS-CoV-2 it is important to assess the individual virus lineages (22), especially with the Omicron variant, as substantial virological changes have occurred as the pandemic has proceeded. Based on the timing of the study, we sampled infections caused predominantly by pre-VOC SARS-CoV-2 (from the B.1 lineage, spanning both S:G614G and S:614D).…”
Section: Discussionmentioning
confidence: 99%
“…For faecal swabs, polyvinylpolypyrrolidone (PVPP) was added to the L6 buffer. When requested, we performed bespoke serological testing using a pseudotype-based virus neutralisation assay (PVNT) to detect neutralising antibodies against the spike protein of SARS-CoV-2 B.1/D614G, Alpha, Delta and Omicron BA.1, as applicable, as described previously [ 19 , 40 , 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…In the UK, none of 96 cat serum samples tested between March and April 2020 possessed neutralising antibodies against SARS-CoV-2, whereas two of 90 (2.2%) collected in January 2021 were positive [ 18 ]. Samples submitted to the Veterinary Diagnostic Service (VDS) at the University of Glasgow between April 2020 and February 2022 showed an overall seroprevalence of neutralising antibodies of 3.2% [ 19 ]; the three-month period with the highest seroprevalence, 5.3% in September–November 2021, occurred during the Delta wave. Taken together, these studies indicate that the rate of SARS-CoV-2 infection in cats increased between the start of the pandemic and the Delta wave.…”
Section: Introductionmentioning
confidence: 99%